2012
DOI: 10.1371/journal.pone.0030585
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variant in miR-196a2 Increased Digestive System Cancer Risks: A Meta-Analysis of 15 Case-Control Studies

Abstract: BackgroundMicroRNAs (miRNAs) negatively regulate the gene expression and act as tumor suppressors or oncogenes in oncogenesis. The association between single nucleotide polymorphism (SNP) in miR-196a2 rs11614913 and the susceptibility of digestive system cancers was inconsistent in previous studies.Methodology/Principal FindingsAn updated meta-analysis based on 15 independent case-control studies consisting of 4999 cancer patients and 7606 controls was performed to address this association. It was found that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 42 publications
6
66
2
5
Order By: Relevance
“…Similar results were obtained from the other two previous meta-analyses, which focused on the effects of rs2910164 and rs11614913 polymorphisms on cancer susceptibility (Qiu et al, 2011;Xu et al, 2011a). Conversely, a meta-analysis based on 15 independent casecontrol studies conducted by Guo et al (2012) suggested that rs11614913 in miR-196a-2 may contribute to increased liver cancer risk. In view of these conflicting results from previous studies and the insufficient statistical power in the previous meta-analyses, we performed the present meta-analysis to update previous meta-analyses, as well to provide a more comprehensive and reliable conclusion on the association between functional polymorphisms in miRNAs and susceptibility to liver cancer.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were obtained from the other two previous meta-analyses, which focused on the effects of rs2910164 and rs11614913 polymorphisms on cancer susceptibility (Qiu et al, 2011;Xu et al, 2011a). Conversely, a meta-analysis based on 15 independent casecontrol studies conducted by Guo et al (2012) suggested that rs11614913 in miR-196a-2 may contribute to increased liver cancer risk. In view of these conflicting results from previous studies and the insufficient statistical power in the previous meta-analyses, we performed the present meta-analysis to update previous meta-analyses, as well to provide a more comprehensive and reliable conclusion on the association between functional polymorphisms in miRNAs and susceptibility to liver cancer.…”
Section: Introductionsupporting
confidence: 86%
“…These miRNAs have long been recognized as targets of genomic lesions, which can frequently activate oncogenes and inactivate tumor suppressors in liver cancer cells such as amplification, deletion, and epigenetic silencing through critical functions downstream of oncogene or tumor suppressor signaling pathways (Ferracin et al, 2010). Some previous casecontrol studies and meta-analyses have suggested that common genetic variants in miRNAs may play important roles in the development of liver cancer (Gao et al, 2009;Qi et al, 2010;Xu et al, 2011a;Guo et al, 2012;Liu et al, 2012b;Zhang et al, 2012), while other investigations have not found any convincing evidence of these polymorphisms in increasing susceptibility to liver cancer (Akkiz et al, 2011b,c;Qiu et al, 2011;Xu et al, 2011a;Zhang et al, 2011;Wang et al, 2012c;Zhou et al, 2012). This controversy could be explained by several reasons, such as the differences in study designs, sample size, ethnicity of subjects, source of controls, genotype methods, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a meta-analysis focusing on one specific type of cancer may increase the stability of the conclusions. Thus far, only two meta-analyses investigated the association between rs11614913 and CRC by means of subgroup analysis (32,36). Those results were consistent with ours in the allele frequency comparison (C allele vs. T allele), co-dominant model (CC vs. TT) and recessive model (CC vs. TT+CT).…”
Section: Discussionsupporting
confidence: 84%
“…Ten previous meta-analyses reviewed the potential role of polymorphism rs11614913 in the development of cancer, seven of which reported a statistically significant association between this polymorphism and susceptibility to cancer without pre-specified tissue origin (27)(28)(29)(30)(31)(32)(33) and three focused on a pre-specified cancer type, such as breast cancer (34), hepatocellular carcinoma (35) or digestive system cancer (36). However, clinical heterogeneity due to inherent differences between cancers of distinct tissue origins may limit the reliability of the conclusions of those meta-analyses (35).…”
Section: Discussionmentioning
confidence: 99%
“…Quality assessment. The quality of included studies was assessed independently by two investigators by scoring according to a "methodological quality assessment scale" (see Supplementary Table S4 online), which was modified from previous meta-analyses (19,20). In the scale, five items, including the representativeness of cases, source of controls, sample size, quality control of genotyping methods and Hardy-Weinberg equilibrium were carefully checked.…”
Section: Systematic Reviewmentioning
confidence: 99%